NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM SERAT SASTRA GENDHING - Nasri Kurnialoh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2015)
Education in the broadest sense, plays an important role in everysociety and culture. Where each community has a regularity that is bound by a value system which lives in its culture. Culture as education proceeds, may be embodied in various forms, so it is interesting to observe and study more deeply the views of a wide range of viewpoints, so that we can understand the meaning contained in an event. Sultan Agung Hanyakrakusuma as king, poet, and artist who have made a great contribution to the Islamic Mataram kingdom. He figures that have a high sensitivityto the problems of the nation and religion One contribution is theessay book entitled Literature Gendhing teaches about inner and outer harmony and the beginning of the end. Harmony between the universe Gumelar with gumulung universe, in terms of the sharpness of this spirtitual, Sultan Agung a degree commensurate with the trustee. Spiritualism Sultan Agung which will be investigated in this study are the values of Islamic religious education in the works, Literature Gendhing.Â Pendidikan dalam arti yang luas, memegang peranan sangat penting dalam setiap masyarakat dan kebudayaannya. Dimana setiap masyarakat mempunyai keteraturan yang diikat oleh sistem nilai yang hidup dalam kebudayaan yang dimilikinya. Kebudayaan sebagai pendidikan yang berproses, dapat diwujudkan dalam beragam bentuk, sehingga sangatlah menarik untuk dicermati dan diteliti lebih mendalam dengan dilihat dari berbagai macam sudut pandang, sehingga kita dapat memahami makna yang terkandung dalam sebuah peristiwa. Sultan Agung Hanyakrakusuma sebagai raja, sastrawan, dan seniman yang telah memberikan kontribusi yang besar pada kerajaan Mataram Islam. Ia tokoh yang memiliki kepekaanyang tinggi terhadap masalah bangsa dan agamanya. Salah satu sumbangsihnya adalah kitab karangannya yang berjudul Sastra Gendhing mengajarkan tentang keselarasan lahir batin dan awal akhir. Keserasian antara jagad gumelar dengan jagad gumulung, ditinjau dari ketajaman spirtitual ini, Sultan Agung mendapat gelar yang sepadan dengan wali. Spiritualisme Sultan Agung yang akan di teliti dalam penelitian ini adalah nilai-nilai pendidikan agama Islam dalam karya, Sastra Gendhing.